Timothy Ong [Brunei, Chairman of Asia Inc Forum] - Ong, Timothy (Institutional Knowledge at Singapore Management University, 2015)
Timothy Ong is Chairman of Asia Inc Forum, a regional platform for policy and business dialogue which he set up after the failure of his magazine Asia Inc. Mr Ong talks openly to DNA about the Asia Inc episode and how he learned from those mistakes to build a stronger, better company. He also shares his impressions of leaders he has met through his work at Asia Inc Forum.